2008
DOI: 10.1007/s11119-008-9057-1
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of multi-disciplinary research in precision agriculture: site-specific management zones in the semi-arid western Great Plains of the USA

Abstract: Researchers from Colorado State University, in collaboration with scientists from the United States Department of Agriculture (USDA), initiated a long-term multidisciplinary study in precision agriculture in 1997. Site-specific management zones (SSMZ) were investigated as a means of improving nitrogen management in irrigated maize cropping systems. The objective was to develop precise nutrient management strategies for semi-arid irrigated cropping systems. This study was conducted in five fields in northeaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…The N application rates were based on various site-specific management zones that were previously delineated on this field as part of a large multi-disciplinary project. Details of the management zone delineation process can be found in Khosla et al (2002Khosla et al ( , 2008. The N application amounts were determined by the N rate algorithm according to Mortvedt et al (1996) for each management zone.…”
Section: Methodsmentioning
confidence: 99%
“…The N application rates were based on various site-specific management zones that were previously delineated on this field as part of a large multi-disciplinary project. Details of the management zone delineation process can be found in Khosla et al (2002Khosla et al ( , 2008. The N application amounts were determined by the N rate algorithm according to Mortvedt et al (1996) for each management zone.…”
Section: Methodsmentioning
confidence: 99%
“…According to KHOSLA et al (2008), who conducts a research related to PA viability, there are some unknowns from producers that ultimately hinder its use in a more expressive way. Among the questions asked by the researcher, there are included some as: 1) Is it possible to determine the spatial variability of attributes in a less costly way?…”
Section: Introductionmentioning
confidence: 99%
“…By integrating remote sensing with precision conservation tools, the effectiveness of conservation practices can be improved and the impact of agriculture on the environment can be reduced. Management zones can also be integrated when applying precision conservation techniques to increase nitrogen use efficiency and reduce nitrate leaching losses without decreasing yields, as shown by earlier work from Khosla et al (2002Khosla et al ( , 2008, , and Inman et al (2007Inman et al ( , 2008. Galzki et al (2011) found that LIDAR provides very precise terrain attributes that can be used to identify environmentally sensitive areas for targeted conservation practices (e.g., grassed waterways, buffer strips, and/or the retirement of land from cultivation or application of conservation tillage).…”
Section: Special Issue Papersmentioning
confidence: 99%